The effect of physical activity on markers of oxidative and antioxidant stress in cancer patients: a systematic review and meta-analysis - Laerte Jônatas Leray Guedes; Victória Brioso Tavares; Saul Rassy Carneiro; Laura Maria Tomazi Neves (BMC Cancer)
Abstract Background Prescribing physical exercise as part of the clinical treatment of cancer patients has become an important strategy in the therapeutic arsenal available in the main health centers specialized in neoplastic diseases, but there is still uncertainty regarding the role of regular physical activity in modifying oxidative stress markers and antioxidants, as high levels of oxidative stress can lead to the development of carcinogens. Therefore, we assessed the effect of physical activity versus absence of physical activity on markers of oxidative stress and antioxidants in cancer patients. Methods We looked for randomized controlled trials that included adult with any type of cancer performing some physical activity and compared them to a control group of cancer patients with no physical activity. The outcomes of interest collected were markers of oxidative stress and antioxidants. Six databases were used for the search (EMBASE, The Cochrane Library (CENTRAL), US National Library of Medicine (PubMed), Physiotherapy Evidence Database (PEDro), Cumulative Index of Nursing and Allied Health (CINAHL) and SPORTDiscus via EBSCO) until January 31st, 2024. Results In the end, 7 randomized controlled clinical trials were included, totaling 573 participants. It was possible to conduct a meta-analysis with demonstrated that physical activity potentially increases the antioxidant marker Trolox, Taoc, Gpx, (SMD = 1.23, CI: 0.13 to 2.34). However, these findings were classified as having very low to moderate GRADE evidence. Conclusion Cancer patients who participated in physical activity programs may have exhibited an increased concentration of antioxidants. Although the overall quality of the evidence in the studies was very low, these findings represent an important field of research that should be guided by studies with more participants and homogeneous methods of analysis of oxidant stress and antioxidant markers. Trial registration PROSPERO CRD42021257815.